SEARCHING FOR ESP TEACHING MODELS TO MATCH THE TEXT-BASED INSTRUCTION FOR SENIOR SECONDARY VOCATIONAL SCHOOLS - Hidayatulloh, Sibakhul Milad Malik (IJIET (International Journal of Indonesian Education and Teaching), 2022)
Students at vocational high school are expected to have proper English proficiency along with their vocational skill. However, Indonesian government has already set the teaching model to be Text-based Instruction (TBI) which is same with senior high school. As a result, English lesson for vocational school indicated as less purposeful. Therefore, this paper is intended to design appropriate teaching model in ESP to be integrated with the teaching cycle in TBI. By reviewing underlaying theories from TBI, and Teaching model in ESP, this paper proposed two teaching model combined with TBI. The first integration is integrating TBI with the practices of Flipped Learning Model in which the activities are divided into two phases namely before classroom time and inside classroom time. The second integration is integrating TBI with the phases of Project Based Learning in which the activities will be divided into four phases. The two proposed teaching model will be useful for promoting writing activities for students. Finally, by proposing those teaching models, it is expected that the practice of English lesson in vocational school will meet its objectives.